Identification of Novel Sesamol Dimers with Unusual Methylenedioxy Ring-Opening Skeleton and Evaluation of Their Antioxidant and Cytotoxic Activities - Murthy, Sudtha; Mohd Hazli, Ummi Husni Aminah; Kong, Kin Weng; Mai, Chun Wai; Leong, Chee Onn; Abd Rahman, Noorsaadah; Lo, Kong Mun; Chee, Chin Fei (Bentham Science Publishers, 2020)
Background: Sesamol is a widely used antioxidant for the food and pharmaceutical industries. The oxidation products of this compound may be accumulated in foods or ingested. Little is known about its effect on human health. Objective: It is of great interest to identify the oxidation products of sesamol that may be beneficial to humans. This study was undertaken to identify the oxidation products of sesamol and investigate their antioxidant and cytotoxic activities. Materials and Methods: Using the ferricyanide oxidation approach, four oxidation products of sesamol (2, 3, 20 & 21) have been identified. Structural elucidation of these compounds was established on the basis of their detailed NMR spectroscopic analysis, mass spectrometry and x-ray crystallography. Additionally, a formation mechanism of compound 20 was proposed based on high-resolution mass spectrometry-fragmentation method. The antioxidant activities of these compounds were determined by the DPPH, FRAP, and ABTS assays. The in vitro antiproliferative activity of these compounds was evaluated against a panel of human cancer cell lines as well as non-cancerous cells. Results: Two oxidation products of sesamol were found to contain an unusual methylenedioxy ring-opening skeleton, as evidenced by spectroscopic and x-ray crystallographic data. Among all compounds, 20 displayed impressive antiproliferative activities against a panel of human cancer cell lines yet remained non-toxic to non-cancerous cells. The antioxidant activities of compound 20 are significantly weaker than sesamol as determined by the DPPH, FRAP, and ABTS assays. Conclusion: The oxidation products of sesamol could be a valuable source of bioactive molecules. Compound 20 may be used as a potential lead molecule for cancer studies. © 2019 Bentham Science Publishers.